An investigation into the effect of biomass particle size on its torrefaction. (4th June 2012) - Basu, Prabir; Rao, Shailendra; Dhungana, Alok
Abstract Present work examines an important practical aspect of torrefaction that is, the effect of size and shape of biomass on torrefaction. Experiments were conducted on different sizes of Poplar and Oak wood in directly heated torrefaction reactors. Experiments were conducted with 13, 19 and 25 mm diameter Poplar wood with lengths varying from 8 to 65 mm long. Most of the experiments were conducted at 250°C for 60 min in a directly heated convective reactor with limited few in a fluidised bed reactor. Results showed increase in mass and energy yield with increasing particle length but opposite with particle diameter. © 2012 Canadian Society for Chemical Engineering